Faktor - Faktor yang Memengaruhi Purchase Intention O2O Voucher: Studi Pada Pengguna Tiktok - Dinda Mandatain; Ryna Parlyna; Adnan Kasofi; Munawaroh Munawaroh (INDO PUBLISHING, 2026)
The growth of social commerce has encouraged the adoption of the Online-to-Offline (O2O) transaction model, particularly through TikTok, which is widely used by Generation Z in Indonesia. O2O vouchers enable consumers to purchase vouchers online and redeem them directly at offline merchant outlets. Despite their high market potential, the actual purchase intention toward O2O vouchers on TikTok remains relatively limited. This study aims to examine the effects of price sensitivity, ease of use, perceived usefulness, and perceived risk on purchase intention toward O2O vouchers among Generation Z TikTok users in Jakarta. This study employs a quantitative approach using a survey method with 180 respondents selected through purposive sampling. Data were collected via an online questionnaire using a seven-point Likert scale and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4. The results indicate that ease of use and perceived usefulness have a positive and significant effect on purchase intention, with perceived usefulness identified as the most dominant variable. In contrast, price sensitivity and perceived risk do not have a significant effect on purchase intention. These findings suggest that Generation Z’s purchase intention toward O2O vouchers is primarily driven by system convenience and perceived functional benefits rather than by price considerations or perceived risk. Therefore, O2O voucher strategies on TikTok should prioritize transaction simplicity and clear value propositions to enhance sustainable purchase intention.